Convetional Biopsy To EBV Amplification Kit In Quick Diagnosis Of Nasopharyngeal Carcinoma. - Hassan, Shahid (2004)
Nasopharyngeal carcinoma (NPC) is the second most commonly occurring cancer amongst men after lung cancer in Malaysia. The relative frequency in South East Asia and China is reported somewhere around 8% of all malignancies in specialized clinics. It is a leading cancer in Southern China and Hong Kong, the highest concentration being 18% in certain racial areas of the part of the world. On the average the annual incidence in Hong Kong is 23.3 per 100,000 population.